The role of administrative empowerment in reducing job burnout among female public school principals in Jubail governorate - Smadi, Mohammad Abed Latif Mohammad; Alshahrani, Najla Ali Funayyis; Almekhlafi, Mohammad Sarhan Khalid; Alshammari, Mohammad Sakit M. (Frontiers in Education, 2025)
This study aimed to determine the level of administrative empowerment and job burnout among female public school principals in Jubail Governorate, as perceived by the principals themselves, and to explore the correlation between them. A descriptive-correlational research design was employed, utilizing a questionnaire administered to a random sample of 56 female school principals. The findings revealed a high level of administrative empowerment among female principals, with the dimension of influence ranking highest. Conversely, the level of job burnout was found to be moderate, with reduced personal accomplishment ranking first among its dimensions. The study highlights the importance of administrative empowerment dimensions, such as delegation of authority and participation in decision-making, and suggests further research into their individual impact on job burnout. Future studies could also examine the effect of training and development on self-confidence and burnout levels.